1996
DOI: 10.5254/1.3538386
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Defects and the Failure Properties of cis-1,4-Polyisoprenes

Abstract: Inherent flaw sizes were determined from fatigue lifetimes, and from the crack length dependence of the strain energy to break, for four cis-1,4-polyisoprenes compounded to have the same crosslink density and low strain hysteresis. Both techniques indicated that the flaws intrinsic to guayule rubber (GR), and to a lesser extent conventional natural rubber, are larger than those found in deproteinized NR. This result may not be surprising; however, the failure properties of the elastomers, expected to depend on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…DPNR exhibits the worst fatigue properties. These results are consistent with an earlier comparison of these rubbers at a fixed crosslink density (single value of modulus = 1 MPa), 25 in which the failure performance was in the order GR > RSS > DPNR. This rank ordering parallels the strain-crystallizability of the rubbers, 35 indicating that the non-polymeric contaminants nucleate crystallization.…”
Section: Unfilled Elastomerssupporting
confidence: 82%
See 4 more Smart Citations
“…DPNR exhibits the worst fatigue properties. These results are consistent with an earlier comparison of these rubbers at a fixed crosslink density (single value of modulus = 1 MPa), 25 in which the failure performance was in the order GR > RSS > DPNR. This rank ordering parallels the strain-crystallizability of the rubbers, 35 indicating that the non-polymeric contaminants nucleate crystallization.…”
Section: Unfilled Elastomerssupporting
confidence: 82%
“…We have shown that GR and NR of relatively low purity have better failure properties, at least as unfilled (gum) networks at a single crosslink density, than purer grades of natural rubbers. 25 Such a result is due to the enhancement of strain-crystallization by the non-polymeric ingredients of the material. 35 In the present work, we extend the comparison to rubbers having a range of crosslink densities, and also examine the effect of carbon black on the relative performance.…”
Section: Rubber Chemistry and Technologymentioning
confidence: 99%
See 3 more Smart Citations